M3 Money Demand and Excess Liquidity in the Euro Area - Christian Dreger; Jürgen Wolters (Public Choice, 2010)
Recent empirical studies have found evidence of unstable long run money demand functions if recent data are used. If the link between money balances and the macroeconomy is fragile, the rationale of monetary aggregates in the ECB strategy has to be doubted. In contrast we present a ``stable'' long run money demand relationship for M3 for the period 1983-2006. To obtain the result, the short run homogeneity restriction between money and prices is relaxed and a break in the income elasticity of money demand after 2001 is taken into account. Measures of excess liquidity do not show significant inflation pressures.
Additional information: The final publication is available at Springer via http://dx.doi.org/10.1007/s11127-010-9679-5. This publication was produced as part of the FINESS project, funded by the European Commission through the 7th Framework Programme under contract no. 217266 (http://www.finess-web.eu/).; info:eu-repo/grantAgreement/EC/FP7/217266
Keywords: C22; C52; E41; 330; Cointegration analysis; error correction; excess liquidity; monetary policy; money demand